2005
DOI: 10.1166/jnn.2005.166
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Assisted Synthesis of Gold Nanoparticles and Their Self-Assembly

Abstract: A novel gold nanoparticle-tripeptide (GNP-tripeptide) conjugate was prepared by peptide in-situ redox technique at ambient temperatureusing a newly designed tripeptide. This new tripeptide was nso designed that it has a C-terminus tyrosine residue, which reduced Au+3 to Au, and the terminally located free amino group was bound to the gold nanoparticle (GNP) surface resulting in highly stable Au colloids. The average diameter of the tripeptide-stabilized GNP is 8.7 +/- 2.3 nm. Tripeptide bound gold nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 0 publications
0
79
0
1
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Recently, there has been increasing interest in the development of biological synthesis for Au NPs because of the need for an environmentally acceptable solvent system and eco-friendly reducing and capping agents. [26][27][28] Xie et al first demonstrated the synthesis of highly fluorescent protein-stabilized Au NCs using a bovine-serum alubumin (BSA)-templated method. 22 The as-prepared Au NCs consisted of 25 gold atoms (Au25) with a red emission at 640 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Recently, there has been increasing interest in the development of biological synthesis for Au NPs because of the need for an environmentally acceptable solvent system and eco-friendly reducing and capping agents. [26][27][28] Xie et al first demonstrated the synthesis of highly fluorescent protein-stabilized Au NCs using a bovine-serum alubumin (BSA)-templated method. 22 The as-prepared Au NCs consisted of 25 gold atoms (Au25) with a red emission at 640 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[10] In our previous work we have reported the formation of GNPs and their self-assembly using a tyrosine-containing short peptide. [11] To the best of our knowledge, nobody has reported the role of tyrosine in the formation of metal nanoparticles in detail. It has been reported that tyrosine has an important function in electron transfer in the photosystem II (PSII), a vital process in nature leading to a neutral tyrosyl Abstract: Synthetic oligopeptides containing redox-active tyrosine residues have been employed to prepare gold and silver nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Bhattacharjee et al 18 reported an approach to prepare colloidal GNP-tripeptides through an in situ tyrosine reduction technique. The designed tripeptide sequence was H2N-Leu-Aib-Tyr-OMe (Aib is 2-aminoisobutyric acid, or 2-methylalanine); tyrosine was included at the C-terminus to act as an electron-transfer agent.…”
Section: Chemical Reductionmentioning
confidence: 99%